Development E-Text Interactive For Learning Indonesian Vocabulary For Class 3 Primary School Students - Setiowati, Theresa Dewi; Degeng, I Nyoman Sudana; Degeng, Made Duananda Kartika (Universitas Negeri Malang, 2024)
Vocabulary plays an important role in language skills, one of which is understanding reading. E-text Interactive is a choice of teaching media that can be used for vocabulary learning. However, e-text Interactive activities developed for learning Indonesian vocabulary are still limited. This development aims to produce e-text interactive with features to facilitate learning Indonesian vocabulary and determine the increase in student learning outcomes after using it e-text interactive. The 4D model by Thiagarajan was used in this development, but was carried out until the development stage. Development involves expert testing and product testing on small and large groups. The development results show e-text interactive is very suitable for use for vocabulary learning, and is successful in improving students' vocabulary learning outcomes. Development e-text interactive can then use more innovative interactive features and develop them for learning vocabulary in other languages. Keywords: Interactive E-text; Voc